A Bibliometric Analysis of Carbon Allowances in the Carbon Emissions Trading Market - Ziyu Li; Bangjun Wang (Energies)
The carbon emissions trading market is an important policy tool for the implementation of the “double carbon” goal, and the study of carbon emission quotas is an important topic for promoting green transformation, energy savings, and emission reduction in enterprises. This paper surveys the development and construction history of China’s carbon trading market, uses the VOS-viewer measurement tool to analyze the keywords co-occurrence and evolution trend of the literature about the carbon trading market from 2005 to 2024, analyzes the research hotspots, and reviews the principles of the initial carbon quota allocation, carbon quota distribution methods, and the carbon trading market carbon quota mechanism under the model construction, etc. The following conclusions can be drawn: (1) The most commonly used principles for allocating initial carbon quota are the principle of equity, the principle of efficiency, and the principle of synthesis. The equity principle focuses on the capacities and burdens of different participants; the efficiency principle maximizes incentives for participants to reduce carbon emissions; the comprehensive principle allocates carbon allowances from the perspective of enterprises, with less consideration for social responsibility and economic benefits. (2) In terms of carbon quota allocation, the initial quota should be gradually tightened, and the proportion of paid quotas should be increased. (3) The types of participants in the carbon emission reduction supply chain model are relatively simple. This paper analyzes the current situation of the research on carbon emission quota, discusses its development rules and problems, and puts forward theoretical and practical suggestions for the better development and construction of China’s unified carbon market in the future.